Social Capital in Community-Based Waste Bank Management - Shafiera Amalia (Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
The waste bank is an innovative method to increase knowledge and behaviour to manage household waste. As a collective action at the community level, social capital has a vital role in the management of the waste bank. This study aims to identify and analyse how the level of trust, network, and social norms play a role in creating a sustainable, community-based waste bank management. This research used the qualitative approach and descriptive method. The data collection techniques were carried out using observations, literature studies, and in-depth interviews. The data were analysed using a qualitative-descriptive technique. The study shows that The Lintas Winongo Waste Bank is a community-based waste bank because it was established and managed by community members in RW 11, Bumijo Urban Village, Yogyakarta City. The manager of Lintas Winongo Waste Bank collaborates with several actors to support the management of the waste bank. The Lintas Winongo Waste bank management requires trust between the actors because it is related to the flow of money. The trust between the actors is built through the transparency of the waste bank management process. The network has a role in exchanging information and providing access to various resources required. The strategies to build networking with the actors are communication, shared understanding regarding the purpose of the waste bank, and a shared commitment to support the waste bank management. The social norms are required to maintain the transparency process and trust between the actors. Moreover, the social norm can build awareness of the citizens to manage domestic waste.